Pengembangan Modul Pjok Berbasis Qr Code dengan Materi Modifikasi Permainan di SMP IT An'nida Kota Lubuklinggau - Darsi, Helvi; Salman, Erick; Malasari, Citra Azhariat; Martiani, Martiani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the development of a QR code-based Corner Module Development with Game Modification Material at SMP IT An'nida, Lubuklinggau City. The method used in this research is the Research and Development method, which uses several instruments that can support research to obtain data or information. The questionnaire was prepared using a Likert scale. The results of this research show that the quality of the module seen from the validity aspect is included in the valid category, the results of the language expert's assessment with a score of 0.861, the results of the material expert's evaluation with a score of 0.8, while the results of the media expert's assessment with a score of 0.807. The quality of the module seen from the practical aspect is categorized as very practical; the results of the teacher response practicality assessment were a score of 4, the results of the one-to-one practicality test were a score of 3.8, while the results of the small group test were with a score of 4.0. From the research we have carried out, we will produce scientific works such as bar-isbn teaching materials and the accredited national journal Sinta 3. In conclusion, the game modification module was developed using the 4-D model, including 4 stages, namely, Defining (planning), DesigningDesign (Design), Developing (development), and Disseminating (deployment). The results of the validity of the modules developed from the results of assessments by experts (linguist experts, material experts, media experts) are categorized as high validity, and the results of the teacher practicality questionnaire can be classified as very practical. Keywords: Development, Game Modification, QR-Code